The recent history of primary and secondary education in the Colombian Caribbean: The case of the Department of Atlántico - Correa Hernández, Gustavo Humberto; Parra Heredia, Juan David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article makes a historiographical contribution to the debate on educational lags in the Colombian Caribbean. The analysis focusses on the case of the Department of the Atlántico and explores the process of formation of its education institutions based on the study of departmental ordinances published between 1980-2014. The first section of the article recounts relevant historical events that help to understand the configuration of Colombia's current school system and that serves as a point of reference to interpret regional educational dynamics during the period of study. The narrative is built from the reading of primary sources, and its contrast with secondary material allows to identify the few incentives that have important educational actors such as public officials, principals, and teachers to promote more educational planning practices in context. Although these findings must be verified with other sources to enhance their explanatory power, they establish analytical bases to discuss the educational problems in the north of the country